THE STRUCTURALLY FUNCTIONAL ANALYSIS OF THE CATEGORY "SOCIAL MECHANISM" IN MODERN PRACTICE OF MANAGEMENT - O. Maksimova; V. Maslikov (Вестник университета)
The purpose of article consists in disclosure of structure and the content of the category "social mechanism". Carrying out the structurally functional analysis of this category, the author elements of the social mechanism, its function and value in modern practice of management reveal.